A função do avô na família monoparental feminina. - Viturino, Maria Mirtes Magalhães (2017)
The relationship between grandparents and grandchildren has been being longer, due to the increase of people's life expectancy, and this relationship is supposed to be beneficial for both generations. In single-parent families headed by women, the grandparents participation has been common, mainly for the care of the grandchildren. This family arrangement is featured by paternal absence, with more intense investment in the affective exchanges between mothers and children, as well as grandparents and grandchildren. The maternal or paternal grandfather, plays an important role in sustaining family dynamics through this support, in general. This research had as its general objective describing the grandfather's function at the female one-parent family, over their perspective. And as specific objectives: analyzing how characterized the coexistence of the grandfathers with the grandchildren is, coming from single-parent female families; Identifing feelings and perceptions arising from this relationship; Listing activities that grandparents and grandchildren do together and how frequently these activities take place; Understanding the grandparents' perception of the mother's mediation over their relationship with their grandchildren. An exploratory descriptive study was carried out and the nature of the research was qualitative. The respondents were eight grandfathers who had a daughter heading a single parent family, regardless of age and schooling, with the majority belonging to the average socioeconomic level. They answered to a biosociodemographic questionnaire and a semi-structured interview. The results revealed that grandparents take the relationship with the grandchildren with great consideration, as well as their protagonism in this type of family configuration through the care, financial aid, frequency of contact and activities performed with the grandchildren was evidenced. It is possible to perceive a preference and greater proximity with these, perhaps as a way to compensate or minimizing the paternal absence, which corroborates the literature. In their perception, there is a good relationship with the daughter, there has been only one case where there is conflict. It demonstrates that they have shown themselves to be accepted and valued by their daughters and grandchildren, feeling especially responsible for them, in general.